Aplicación e integración de mercado en los procesos administrativos del almacén Je Pinos. - Tobar Peña, Johnny Jamil (My University, 2018)
Marketing today is a discipline that helps the business sector to determine consumer needs and requirements. In addition, it is a tool that facilitates the management of generating, creating, raising awareness of products of value for customers, partners and society in general. The company taken as object of study, offers products and varied services for the home. In the absence of effective marketing strategies within their administrative processes, the aforementioned topic was made feasible and a scientific study was conducted through interviews with companies with similar characteristics within the environment, studies that aim to demonstrate which are the most suitable strategies to be applied and integrated within mentioned processes. The strategies of digital marketing, internal marketing and marketing at the point of sale are the most productive at present, therefore, tasks will be determined to be fulfilled within the administrative processes and obtain a better local positioning of the company. To be applied within the administrative process, we take as reference the four stages of this procedure, such as planning, organization, direction and control, in this way the study aims to integrate marketing strategies in a more organized way and that is convenient to obtain effectiveness and efficiency.
El mercadeo hoy en día es una disciplina que ayuda al sector empresarial a determinar necesidades y requerimientos de consumidores. Además, es una herramienta que facilita la gestión de generar, crear, concientizar productos de valor para clientes, socios y la sociedad en general. La empresa tomada como objeto de estudio, ofrece productos y servicios variados para el hogar. Ante la inexistencia de estrategias de marketing efectivas dentro de sus procesos administrativos, se viabilizó el tema mencionado y se realizó un estudio científico mediante entrevistas a empresas con similares características dentro del entorno, estudios que pretenden demostrar cuáles son las estrategias más idóneas por aplicarse e integrarse dentro de mencionados procesos. Las estrategias de marketing digital, marketing interno y marketing en el punto de venta son las más productivas en la actualidad, por lo tanto, se determinarán tareas para ser cumplidas dentro de los procesos administrativos y obtener un mejor posicionamiento local de la empresa. Para ser aplicadas dentro del proceso administrativo se tomó como referencia las cuatro etapas de este procedimiento, como son planificación, organización, dirección y control, de esa manera el estudio pretende integrar las estrategias de mercadeo de una manera más organizada y que resulte conveniente para obtener eficacia y eficiencia.
Keywords: MARKETING; CONSUMIDORES; PROCESOS ADMINISTRATIVOS; ESTRATEGIAS